APLIKASI PEMBERIAN GULA NIRA KELAPA DALAM MENINGKATKAN KADAR HEMEGLOBIN (HB) PADA REMAJA PUTRI YANG MENGALAMI ANEMIA - Indrayani, Siska; Miftahurrahmi, Miftahurrahmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This research was conducted to analyze the effect of giving coconut juice in increasing hemeglobin levels in adolescent girls who have anemia. This type of quasi- experimental research using one group pretest and posttest methods, uses one group before and after being given an intervention to determine the effect of coconut palm sugar on increasing hemeglobin levels. Analysis of the data used by paired sample T- test if the data are normally distributed to analyze the effectiveness of consumption of palm sap in increasing hemeglobin levels in adolescents. The results of the study have been obtained from the results of statistical tests that the value of p value 0,000 so that it can be concluded that there is an increase in hemeglobin levels after the giving of palm sap. Based on the results of statistical tests this study shows that consuming coconut palm sugar in seven days can increase Hb levels by 1.79 gr / dl in adolescents who have anemia. The increase in hb levels was significant enough so that the researchers argued that consuming coconut palm sugar can overcome the problem of anemia in adolescents.